Effect of home telehealth care on blood pressure control: A public healthcare centre model. (January 2019) - Lu, Ju-Fen; Chen, Ching-Min; Hsu, Chien-Yeh
Objective: This study aimed to evaluate the effectiveness of home telehealth care combined with case management by public health nurses, in improving blood pressure control in patients with hypertension. Methods: This cohort study examined the data of patients with hypertension obtained from a telehealth service centre database, between July 2011– June 2012. Eligible patients were adults (≥40 years old) with both prehypertension and hypertension, living alone or in the remote suburbs of metropolitan areas. Demographic data were collected from 12 district public health centre in Taipei, Taiwan. Following enrolment, patients received an appropriate and validated home telehealth device kit for automatic blood pressure monitoring and automated modem via a telephone line or a desktop computer with Internet connection to enable data transmission between the patient's home and telehealth service centre. Patients were instructed to upload the measured data immediately every day. The study outcomes included blood pressure and home telehealth service utilisation. Results: Of the 432 patients recruited, 408 (94%) completed data collection. Linear regression analysis found an average 22.1 mm Hg reduction in systolic blood pressure after one year. The mean slope of systolic blood pressure was classified as decreased or non-decreased. An systolic blood pressure decreasing trend was observed in 52.2% patients, while 47.8% patients showed an increasing systolic blood pressure trend. Patients in the decreased systolic blood pressure group tended to be older ( p = 0. 0001), with a greater proportion of hypertension alarms ( p = 0. 001), improved self-blood pressure monitoring behaviour ( p = 0.009) and higher self-measured blood pressure monitoring frequency ( p = 0. 010). Patients in the decreased systolic blood pressure group had a higher self-measured blood pressure monitoring frequency (odds ratio = 0.95, 95% confidence interval, 0.91–0.99, p = 0. 013) than their counterparts. Conclusions: Home telehealth care combined with care management by public health nurses based in public health care centre was feasible and effective for improving blood pressure control among patients with hypertension. Further studies should conduct a thorough analysis of the cost-effectiveness of this intervention. A randomised controlled trial with a longer follow-up period is required to examine the effects of the improved home telehealth device kit on the care of patients with hypertension.